Geographical Landscape and Transmission Dynamics of SARS-CoV-2 Variants Across India: A Longitudinal Perspective - Jha, Neha; Hall, Dwight; Kanakan, Akshay; Mehta, Priyanka; Maurya, Ranjeet; Mir, Quoseena; Gill, Hunter Mathias; Janga, Sarath Chandra; Pandey, Rajesh (Frontiers in Genetics, 2021)
Globally SARS-CoV-2 has moved from one tide to another with ebbs in between. Genomic surveillance has greatly aided the detection and tracking of the virus as well as the identification of the Variants of Concern (VOC). The knowledge and understanding from genomic surveillance is important for a populous country like India for public health and healthcare officials for advance planning. An integrative analysis of the publically available datasets in GISAID from India reveals the differential distribution of clades, lineages, gender and age over a year (Apr 2020-Mar 2021). The significant insights include the early evidence towards B.1.617 and B.1.1.7 lineages in the specific states of India. Pan-India longitudinal data highlighted that B.1.36* was the predominant clade in India until January-February 2021 after which it has gradually been replaced by the B.1.617.1 lineage, from December 2020 onwards. Regional analysis of the spread of SARS-CoV-2 indicated that B.1.617.3 is first seen in India in the month of October in the state of Maharashtra while the now most prevalent strain B.1.617.2 was first seen in Bihar and subsequently spread to the states of Maharashtra, Gujarat and West Bengal. To enable a real time understanding of the transmission and evolution of the SARS-CoV-2 genomes we built a transmission map available on https://covid19-indiana.soic.iupui.edu/India/EmergingLineages/April2020/to/March2021. Based on our analysis, the rate estimate for divergence in our dataset was 9.48e-4 substitutions per site/ year for SARS-CoV-2. This would enable pandemic preparedness with the addition of future sequencing data from India available in the public repositories for tracking and monitoring the VOCs and Variants of Interest (VOI). This would help aid decision making from the public health perspective.